Occupancy satisfaction level and ventilation behaviour in Five types of housing in Putrajaya, Malaysia - Idowu, Ibiyeye Aminat (2014)
As individuals tend to attain desirable comfort level in their homes, the quality of the indoor air in the home is being threatened. To attain this level of comfort, occupants employ mechanical cooling strategy due to the high temperature and humidity they experience. However this comfort could still be attained through proper natural ventilation without jeopardising the indoor air quality (IAQ). Although, natural ventilation has been revealed to be a good alternative to mechanical cooling both from thermal comfort and IAQ perspectives, airconditioner (AC) usage is still prevalent in the home and occupants seldom utilise natural ventilation through window openings. Numerous studies on the utilization of natural ventilation in homes have been conducted but in depth studies of the natural ventilation provisions and occupants’ behaviour towards these provisions in relation to IAQ in hot-humid climate are still very limited. Therefore, this study aims to investigate natural ventilation provisions of residential buildings in hot-humid climate under different terraced house design types, with the following objectives: 1) To identify natural ventilation provisions in selected housing design types with reference to Uniform Building By-Law (UBBL) requirements. 2) To determine the ventilation rates delivered by the natural ventilation provisions in the selected housing design types through computer simulation. 3) To assess occupants’ utilisation of natural ventilation provisions and their level of satisfaction by taking into account the UBBL requirements and the ventilation rates of the building spaces. Five house design types were selected in Putrajaya for the study and natural ventilation provisions were identified through acquired building documents. A total of 298 households from among the selected house design types were surveyed and computer simulations with Integrated Environmental Solution <Virtual Environment> (IES<VE>) were carried out on the entire house types to determine the ventilation rates. Two house design types were found not to comply with the UBBL 10% window area requirement and the level of AC usage was high mostly in the master bedroom. Respondents were found to open windows mostly during the daytime and their level of satisfaction with indoor ventilation when utilizing natural ventilation was found to be significantly related to opening sizes that are in accordance with UBBL, longer duration of opening windows and means of achieving comfort. From the simulation, house types that comply with UBBL 10% window area requirement were found to exhibit higher ventilation rates due to their large opening area. Findings from this study will shed more light on behavioural pattern of occupants of residential buildings towards natural ventilation provisions and highlight the importance of conforming to the law governing the provisions for natural ventilation in residential buildings.